Governance of the smart mobility transition - Marsden, Greg; Reardon, Louise (Emerald points., 2018)
Rapid changes are underway in mobility systems worldwide, including the introduction of shared mobility solutions, Mobility as a Service and the testing of automated vehicles. These changes are driven by the development and application of 'smart' technologies. Transition to these technologies present significant opportunities for countries, cities and rural areas alike, offering the tempting prospect of economic benefit whilst resolving today's safety, congestion, and pollution problems. Yet while there is a wealth of research considering how these new technologies may impact on travel behaviour, improve safety and help the environment, there is a dearth of research exploring the key governance questions that the transition to these technologies pose in their disruption of the status quo, and changes to governance that may be required for the achievement of positive social outcomes. This book aims to step into this void and in doing so presents an agenda for future research and policy action. Bringing together a collection of internationally recognised scholars, drawing on case studies from around the world, authors critically reflect on three primary governance considerations. First, the changing role of the state both during and post-transition. Second, identifying the voices shaping the smart mobility discourse. And third, analysing the implications for the state's capacity to steer networks and outcomes as a result of these transitions. The authors argue that at present there exists a critical window of opportunity for researchers and practitioners to shape transitions and that this opportunity must be seized upon before it is too late.